Common Law, Judicial Precedents and the Nigerian Receivership Procedure. (April 2014) - Adebola, Bolanle
Abstract Before the enactment of the Companies and Allied Matters Act (CAMA) 1990, receivership in Nigeria was governed by case law, informal rules (of practice) and the Companies Decree 1968. Nigerian judges were heavily influenced by British case law, precedents were British and the Nigerian Companies Decree was a transplant of the British Companies Act 1948. Against this background, the Supreme Court of Nigeria delivered the Intercontractors decisions in 1988, which subsequently governed the nature, status and powers of Nigerian receivers. In 1990, CAMA introduced a more robust receivership regime which prescribed the nature, status and powers of the receiver, reversing some of the Intercontractors principles. However, the courts, particularly the Supreme Court, failed to enforce the relevant provisions of CAMA or to examine the applicability of the Intercontractors principles that they conscientiously enforced. This article examines the validity of the Intercontractors principles and their continued relevance under CAMA 2004.